The Incidence of Glenohumeral Bone and Cartilage Lesions at the Time of Anterior Shoulder Stabilization Surgery: A Comparison of Patients Undergoing Primary and Revision Surgery. Issue 10 (August 2018) - Duchman, Kyle R.; Hettrich, Carolyn M.; Glass, Natalie A.; Westermann, Robert W.; ,; Wolf, Brian R.; Baumgarten, Keith; Bishop, Julie; Bravman, Jonathan; Brophy, Robert; Carpenter, James; Jones, Grant; et al.
Background: Intra-articular glenohumeral joint changes frequently occur after shoulder instability events. Purpose: (1) To compare demographic characteristics, baseline patient-reported outcomes, and intraoperative findings for patients undergoing primary or revision shoulder stabilization surgery and (2) to determine the incidence of glenohumeral bone and cartilage lesions in this population while identifying factors independently associated with these lesions. Study Design: Cross-sectional study; Level of evidence, 3. Methods: The Multicenter Orthopaedic Outcomes Network (MOON) Shoulder Group shoulder instability database was used to identify all prospectively enrolled patients undergoing shoulder stabilization surgery for anterior instability between October 2012 and September 2016. Any patient who underwent surgery for posterior or multidirectional shoulder instability or concomitant rotator cuff repair surgery was excluded. Patient demographic characteristics, preoperative patient-reported outcomes, and intraoperative findings, including glenohumeral bone and cartilage lesions, were compared for patients undergoing primary and revision shoulder stabilization surgery. Additionally, patients with and without glenohumeral bone and cartilage lesions were compared and independent associations determined using multivariate analysis. Results: There were 545 patients available for analysis (461/545 [84.6%] primary; 84/545 [15.4%] revision). Patients undergoing revision surgery were older ( P = .001), were more frequently smokers ( P = .022), had a greater number of instability events before surgery ( P = .047), more frequently required reduction assistance ( P < .001), and had lower Short Form–36 (SF-36) Mental Component Summary ( P = .020) and Western Ontario Shoulder Instability Index (WOSI) ( P = .026) scores preoperatively. Additionally, patients undergoing revision surgery had a higher frequency of bone and cartilage lesions than those undergoing primary surgery (47.6% vs 18.4%, respectively; P < .001). Male sex, revision surgery, black race, increasing body mass index, increasing patient age, and lower preoperative SF-36 Physical Component Summary score were independently associated with the presence of glenohumeral bone and cartilage lesions at the time of shoulder stabilization surgery. Revision surgery was strongly associated with the presence of glenohumeral bone and cartilage lesions (odds ratio [OR], 4.381 [95% CI, 2.591-7.406]) and glenoid bone loss greater than 10% (OR, 9.643 [95% CI, 5.128-18.134]) or 20% (OR, 13.076 [95% CI, 5.113-33.438]) of the glenoid width. Conclusion: Glenohumeral bone and cartilage lesions are common at the time of shoulder stabilization surgery, occurring more frequently in patients undergoing revision surgery as compared with primary surgery. On the basis of these findings, future prospective studies should aim to compare the clinical outcomes in these 2 groups.